Correlation of Arterial Blood Gas Value with Outcome of Patient Admitted with Acute Exacerbation of Chronic Obstructive Pulmonary Disease (Nepalese Medical Journal, 2020)
Background: The outcome of Chronic Obstructive Pulmonary Disease depends upon the partial pressure of oxygen and carbon dioxide This study was aimed to find the role of arterial blood gas parameters during the length of hospital stay among patients admitted for Chronic Obstructive Pulmonary Diseasewith acute exacerbation.Materials and Methods: This was an observational study conducted in KIST Medical College Teaching Hospital from February 2017 to August 2019. Patients admitted with the chronic obstructive pulmonary disease were evaluated. Demographic data as well as oxygen saturation (SPO2), pulmonary function test, and arterial blood gas analysis were recorded and analyzed.Results: Among 112 patients, the female to male ratio was 1.38: 1 with 84.8% over 60 years of age. One-third of patients (n=38) had exposure to both tobacco smoking and biomass and of them, 86.8% were females. Mean SpO2 was 75.9% and mean FEV1 was 0.92 L (SD=0.295) and significant association was found (p